Effect of Return On Assets, Return On Equity, and Current Ratio on Stock Returns - Rachmawati, Windasari; Ulya, Naufal; Karim, Abdul (Universitas Semarang, 2023)
The performance of a financial company can affect stock prices where stock prices sometimes experience increases and decreases. The stock price is very influential on stock returns for investors. This study aims to analyze the effect of the independent variables on the dependent variable. The independent variables in this study are Return On Assets, Return On Equity, and Current Ratio. While the dependent variable in this study is stock returns. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The sample selection in this study used a purposive sampling method and obtained a sample of 27 based on certain criteria. The data analysis technique used is multiple linear regression analysis using SPSS 22. The result of this study is significance value of the variabel Return On Assets is 0,099 > 0,05, variable Return On Equity is 0,950 > 0,05, and variable Current Ratio is 0,153, so hyphotesis is rejected. The conclusion of this study that Return On Assets, Return On Equity, and Current Ratio have no significant effect on stock returns.Keywords : Return On Assets, Return On Equity, Current Ratio, stock returns.